Physiological consequences of doublet discharges on motoneuronal firing and motor unit force - Mrówczyński, Włodzimierz; Celichowski, Jan; Raikova, Rositsa; Krutki, Piotr (Frontiers in Cellular Neuroscience, 2015)
The double discharges are observed at the onset of contractions of mammalian motor units (MUs), especially during their recruitment to strong or fast movements. Doublets lead to MU force increase and improve ability of muscles to maintain high force during prolonged contractions. In this review we discuss an ability to produce doublets by fast and slow motoneurons (MNs), their influence on the course of action potential afterhyperpolarization as well as its role in modulation of the initial stage of the firing pattern of MNs. In conclusion, a generation of doublets is an important strategy of motor control, responsible for fitting the motoneuronal firing rate to the optimal for MUs at the start of their contraction, necessary for increment of muscle force.